Peran Digital Parenting terhadap Kesehatan Mental dan Regulasi Emosi Remaja - Retno Chania; Elfira Rosa Karnaini; Nia Putri Cahyani; Yustania Ningsih; Alisyia Guspita; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The rapid development of digital technology has transformed family interactions and created new challenges for parents in supporting adolescents. Digital parenting has emerged as an important approach to promoting adolescents' mental health and emotional regulation in the digital era. This study aims to examine the role of digital parenting in adolescents' mental health and emotion regulation using a Systematic Literature Review (SLR). The review followed the PRISMA guidelines, with relevant articles identified through Google Scholar using predefined keywords. Based on the inclusion and exclusion criteria, 10 articles published between 2016 and 2026 were selected and analyzed using a qualitative descriptive approach. The findings indicate that digital parenting characterized by open communication, active parental involvement, digital mediation, and parents' digital literacy positively contributes to adolescents' emotion regulation and mental well-being. Conversely, digital neglect, ineffective family communication, and limited parental involvement in adolescents' digital activities increase the risk of negative emotions, problematic internet use, gaming addiction, and psychological problems such as anxiety and depression. Furthermore, strengthening parental self-efficacy through psychoeducational programs and web-based interventions has been shown to improve the quality of digital parenting practices. Therefore, effective digital parenting depends not only on limiting screen time but also on fostering warm emotional relationships, empathetic communication, and parents' readiness to guide adolescents in navigating the challenges of the digital environment.